Inflation Inequity and the Measurement of Pro-Poor Growth - Michael Grimm; Isabel Günther (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
Despite the recent and intense debate on how to define and measure pro-poor growth, there is one important issue which has so far not received sufficient attention: how applications of pro-poor growth measurements can appropriately take into account relative price changes, which, given the heterogeneity of consumption patters across the income distribution, often lead to significant inflation inequality. We show that incorporating inflation inequality into pro-poor growth measurements is not only a methodological necessity but if ignored can seriously bias assessments of the pro-poorness of growth. Using household expenditure surveys, we suggest simple methodologies which are able to redress such biases and appropriately reflect the changes of relative prices and the development of the purchasing power of the poor in pro-poor growth measurements. Empirically, we illustrate our concepts for the case of Burkina Faso using growth incidence curves and poverty change decompositions as pro-poor growth measurements.
Keywords: I32; D12; O12; D63; 330; Pro-Poor Growth; Differential Inflation; Burkina Faso